Preoperative graft assessment in aortocoronary bypass surgery - Tinica, Grigore (Exp Ther Med, 2016)
Coronary artery bypass graft (CABG) is a surgical procedure able to improve the blood supply to the myocardium. In the present study, the distal segments of grafts taken from the internal thoracic artery (ITA), radial artery (RA) and saphenous vein (SV) for use in aortocoronary bypass surgery were examined. The morphologies of the grafts were investigated in order to draw conclusions concerning their patency and viability. In addition, clinical and laboratory risk factors considered to be significant predictors of lesion severity in graft vessels used in CABGs were investigated. In total, 54 distal graft segments of ITAs, RAs and SVs from 20 men and 6 women aged between 42 and 78 years, were evaluated. Histological analyses were used to visualize graft lesions. Morphometrically, the intimal thickness index (ITI) and luminal narrowing were assessed as an indication of graft patency. The histological changes observed in the graft vessel walls included the presence of distinct atheromatous plaques (fatty streaks in 2 cases) or thickening of the intima (20 cases) and media (17 cases). Morphometric analysis showed that the mean ITI of the vessel conduits was 0.37 in the SVs, 0.95 in the RAs, and 1.66 in the ITAs. No patient had >50% conduit stenosis. By assessing the association between risk factors and graft lesions, it was found that all the patients showed risk factors for atherosclerosis, such as age (61.54%), arterial hypertension (65.38%), hyperlipidemia (65.38%), smoking (34.61%), diabetes mellitus (38.46%) and obesity (15.38%). The presence of pre-existing lesions in bypass grafts may contribute to a reduction in their viability, particularly in the case of venous grafts. Further long-term follow-ups are mandatory to evaluate the consequences of such lesions upon the patency of the grafts.